MENCERMATI POTENSI KABUPATEN SRAGEN MENUJU PEREKONOMIAN BERKUALITAS - Agusthina Ouwpoly; Lilis Anisah (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2018)
The data results of the Economic Census 2016 (SE2016) are one of the capital in measuring the strength of the non-agricultural nation’s economy and can be one of the basis in determining economic policy. Descriptive statistical analysis was used in this study to examine more deeply the potential of Sragen Regency in two-digit the Indonesian Standard Industrial Classification (the KBLI). Results show that G, C and I categories are the dominant categories in terms of the number of establishments and workers. More than 80 percent of business activities and labor are absorbed in category G run by business code-coded KBLI 47, the rest is run by them in the KBLI 46 and 45 codes. In terms of the number of establishments, KBLI code 14, 10 and 13 are found to be the three major economic activities in Sragen Regency for C category. It is also found that, in terms of workers absorbence, KBLI code 10, 13 and 14 are the major codes in that category. The third dominant position is taken by I category shows that the needs of Sragen Regency people for Accomodation & Food Service Activities (I category) become promising business opportunities. More than 95 percent of business activities and workers are absorbed in I category run by 56 KBLI code establishment players, the rest is run by them in the 55 KBLI code.